Evaluation of excavator technologies: application of data fusion based MULTIMOORA methods - Altuntas, Serkan; Dereli, Turkay; Yılmaz, Mustafa Kemal (Journal of Civil Engineering and Management, 2015)
Excavators are quite expensive vehicles. Therefore, there may be huge losses for decision makers if a wrong decision is made during the purchasing process. A good evaluation of excavator alternatives both reduces costs and increases the benefits the excavator for the purchaser. The aim of this study is to prioritise excavator technologies to help decision makers during the purchasing process and to apply three different “data fusion methods” instead of the “theory of dominance” of the original MULTI MOORA method. The MULTI MOORA method is composed of three methods, namely: the ratio analysis as a part of MOORA, Reference Point Theory (the reference point approach as a part of MOORA) and the Full Multiplicative Form. It is used to prioritise excavator technologies in this study. The MULTI MOORA method combines three results obtained from these three methods using the theory of dominance. Dominance directed graph, Rank position method and Borda count method as data fusion methods are also used to combine these three results instead of the “theory of dominance”. The results from this study show that there is no difference between the data fusion methods and the MULTI MOORA method can be applied to technology evaluation of the excavator alternatives successfully.